AQM-06: The Macro economic Model of the OeNB - Markus Leibrecht; Martin Schneider (Oesterreichische Nationalbank (OeNB), 2006)
This paper gives an overview of the current version of the quarterly macroeconomic model of the Oesterreichische Nationalbank for Austria. The model is a small to medium size macroeconomic model. It is in the tradition of the neoclassical synthesis and is therefore in line with most models used by euro system central banks. The model has been extended in several ways compared with the previous version. The most important changes concern the use of oil and import competitor's prices in the supply block, a more detailed treatment of government receipts, the use of tax rates as policy instruments as well as a dynamic import demand indicator. In the empirical part, the paper presents some simulation results to show the impact of tax increases on the Austrian economy and the reaction of the model to five standard macroeconomic shocks: Increases of the value added tax, the personal income tax and the corporate income tax by the same amount have different effects on the Austrian economy. The reaction of the model to macroeconomic shocks is characterized by a high demand multiplier and a low negative impact of price competitiveness on exports.
Keywords: C3; C5; E1; E2; 330; Macroeconometric Model; AUstria